Effect of different water levels on rice growth and yield / Norfatin Atikah Jaafarullah - Jaafarullah, Norfatin Atikah (Faculty of Plantation and Agrotechnology, 2018)
Water condition is one of the main concerns in rice production. It is estimated that over 75 percent of world’s rice is produced using continuous flooding practice. The purpose of this study was to investigate the effect of different water level on paddy growth and yield. There are four water treatments with different water levels which are T0 (1 cm), T1 (3 cm), T2 (6 cm) and T3 (9 cm) to clarify the best water level that can give same performance growth and yield as the common water level application by the farmers. The collected parameter data were plant height, number of tillers, number of leaves, relative chlorophyll content, number of panicles, and fresh and dry weight. Completely Randomized Design (CRD) experimental design with five replications was implemented during the experiment. The data retrieved from conducted experiment was analysed by using Minitab software on One-Way ANOVA calculation method. The experiment outcomes show there was no significance difference between the water level on the rice growth. These results suggested that saturated to 1 cm flooding water did not affect rice production and growth. Therefore, it was enough to sustain rice growth production.